Allergen manufacturing and quality aspects for allergen immunotherapy in Europe and the United States: An analysis from the EAACI AIT Guidelines Project. Issue 4 (10th January 2018) - Bonertz, A.; Roberts, G.; Slater, J. E.; Bridgewater, J.; Rabin, R. L.; Hoefnagel, M.; Timon, M.; Pini, C.; Pfaar, O.; Sheikh, A.; Ryan, D.; Akdis, C.; et al.
Abstract: Adequate quality is essential for any medicinal product to be eligible for marketing. Quality includes verification of the identity, content and purity of a medicinal product in combination with a specified production process and its control. Allergen products derived from natural sources require particular considerations to ensure adequate quality. Here, we describe key aspects of the documentation on manufacturing and quality aspects for allergen immunotherapy products in the European Union and the United States. In some key parts, requirements in these areas are harmonized while other fields are regulated separately between both regions. Essential differences are found in the use of Reference Preparations, or the requirement to apply standardized assays for potency determination. As the types of products available are different in specific regions, regulatory guidance for such products may also be available in one specific region only, such as for allergoids in the European Union. Region‐specific issues and priorities are a result of this. As allergen products derived from natural sources are inherently variable in their qualitative and quantitative composition, these products present special challenges to balance the variability and ensuring batch‐to‐batch consistency. Advancements in scientific knowledge on specific allergens and their role in allergic disease will consequentially find representation in future regulatory guidelines. Abstract :